Medical students' experiences of a longitudinal integrated clerkship: a threshold concepts analysis. Issue 6 (2nd November 2021) - Gupta, Shalini; Howden, Stella
ABSTRACT: Longitudinal Integrated Clerkships (LIC) are known to provide several pedagogical advantages including transformational educational experiences. The study explored the learning experience of undergraduate medical students who undertook a rural LIC in a Scottish primary care setting. This paper presents an analysis of the transformative role of LIC placements using the Threshold Concept (TC) theory. This qualitative study gathered students' perceptions of their LIC experience longitudinally through written and audio diaries over a period of 1–2 months. The issues narrated in diaries were followed-up in individual semi-structured interviews. Transcripts were thematically analysed to identify key characteristics of TCs using a criterion-based approach. Data from 12 audio and nine written diaries, and five interviews led to identification of three inter-connected themes associated with the LIC year: professional identity formation, becoming an agentic learner and comfort with uncertainty. These appeared transformative in nature and resembled threshold concepts in their character and effect. An active and legitimate role in the healthcare team, longitudinality and transdisciplinary learning during LIC placements were contributary towards navigating these thresholds. The LIC exposure provided transformative learning experiences, and a stable environment that facilitated acquisition of specific TCs in the medical students' journey towards becoming a doctor. LIC affordances fostered a transformed view of self, which was more confident in dealing with uncertainty, comfortable in the emerging professional identity, and described having enhanced agentic capabilities.